INFLUENCE OF FOLLICULAR AND LUTEAL PHASE ON LEVOFLOXACIN PHARMACOKINETICS IN FEMALE VOLUNTEERS - M.MADHAVI,; U.MARY PRIYANKA, (International Journal of Pharma and Bio Sciences, 2014)
The cyclic changes of menstrual cycle alter the pharmacokinetics of levofloxacin. The effect of follicular and luteal phase on levofloxacin pharmacokinetics was studied in 15 healthy female volunteers taking a single dose of 500mg tablet on day 10th (follicular phase) and day 21 (luteal phase ). Levofloxacin levels in saliva samples at different time points were estimated by HPLC. Follicular phase has high levels of estrogen which has an inhibitory effect on drug metabolism by inhibiting liver microsomal enzymes, where as luteal phase has high levels of progesterone which induces drug metabolism. All results were expressed as Mean±SD, data was analysed using paired t-test followed by Newman Keuls multiple comparison test. A value less than p<0.0001 was considered as statistically significant. The mean salivary concentrations of levofloxacin were decreased in luteal phase compared to follicular due to which bacteria may develop resistance in several infections and diseases may not be cured easily during this phase and may require dosage adjustments.